Socio-Economic Status and Psychological Well-Being in a Sample of Turkish Immigrant Mothers in Germany - Fassbender, Ina; Leyendecker, Birgit (Frontiers in Psychology, 2018)
This study analyzes the relation of socio-economic status and psychological well-being in a sample of 327 Turkish immigrant mothers in Germany. We assessed maternal psychological well-being with the CES-D-10, the Satisfaction with Life Scale, and selected items of the Hassles Scale referring to daily hassles. Mothers' SES was assessed by means of household income and maternal education. The sample has a predominantly low to very low household income. A cluster analysis on maternal education and household income identified three SES-groups: A low-income cluster, a low-education cluster, and a third cluster of mothers who were slightly more advantaged in terms of household income and education. When applying the 10-point criterion of the CES-D-10, the three clusters differed regarding depression. About 40% of the mothers with lowest income and lowest education were depressed, compared to 28% of the more-advantaged cluster. The clusters further differed with respect to daily hassles and life-satisfaction. A higher SES was associated with less daily hassles, a higher life satisfaction, and less depression. This replicates findings of other studies regarding the relation of SES and psychological well-being. A follow-up assessment for about 60% of the mothers after 1 year revealed no changes in the well-being scales for each SES cluster, and a significant multivariate effect of the SES clusters. This suggests that SES is a long-term influential factor on psychological well-being. We discuss our findings in terms of the importance to integrate Turkish immigrant mother into the Germany society and in terms of the importance of maternal psychological well-being for children's positive development.